Rainfall trends in the Lake Victoria Basin, Uganda - Egeru, Anthony (Atmosphere, 2016)
during the months of March-May and October- December; with the winds changing direction to the north ending of the lake. Over the years, rainfall in the basin has fluctuated with debilitating impacts. This is because 80% of the lake’s water input is from rainfall; as such the lake is generally described as an “atmosphere controlled” lake (Tate et al., 2004).. In that regard, the variability of rainfall over the lake both spatially and temporally is important in influencing the lake’s water levels. Research into the spatial and temporal variability of rainfall over Lake Victoria basin have been undertaken by several researches but have shown no significant trends. However, from time to time, dry spells continue to occur over the basin, leading to the necessity to show not only the patterns but the intensity of rainfall variability in the basin as well. In this current work rainfall trends and intensity of variability over the basin in the Uganda part are shown, using data from five weather stations (Masaka, Wakiso, Kampala, Mukono and Jinja). Data covers 35 years (1980-2014).
Keywords: Rainfall trends; Lake Victoria Basin; Uganda